Capacity Measures Explain Only a Small Part of Self-Reported Disability in Institutionalized Ambulatory Older Adults: An Observational Study. (3rd April 2019) - Coutinho, Cristiana; Santos, Sara; Queirós, Alexandra; Silva, Anabela G.
Abstract: Aims: To investigate the association between self-reported disability and capacity-based measures for older adults attending day care centers and nursing homes. Methods: 312 institutionalized ambulatory older adults were assessed for self-reported disability (WHODAS 2.0), capacity-based measures (gait velocity test, timed up and go test (TUG) and grip strength), demographics, pain and depression. Results: Regression models using self-reported disability as the dependent variable and capacity–based measures as the independent variables explained only 5% and 11% of self-reported disability in older adults from nursing homes and day care centers, respectively. When adding to the regression analysis, pain, depression and demographic variables as independent variables, the final model explained 52% of the variance of self-reported disability both in older adults from day care centers and nursing homes. Conclusion: These results show that self-reported disability and capacity-based measures assess very different constructs and highlight the need for interventions targeting pain and depression as a potential mean to improve self-reported disability.